The Influence of Organizational Commitment on Employee Performance Through Job Crafting as a Mediation Variable at Bank Jatim Trenggalek City - Putri, Adhinta Darusancia Anggani; Asfiyah, Nurul; Andharani, Sri Nastiti (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The purpose of this study was to determine the effect of organizational commitment, employee performance, job crafting and whether job crafting is able to mediate the effect of organizational commitment on employee performance. This research was conducted on bank employees with 113 employees as respondents. The sampling technique in this study uses a non-probability technique. The data collection technique was carried out by means of a questionnaire. The data analysis technique uses the statistical t test, Sobel test, and the SPSS 22 program. The results of this study show organizational commitment shows high results, employee performance shows high results, and job crafting shows high results. There is a significant influence between organizational commitment on employee performance, organizational commitment has a significant effect on job crafting, job crafting has a significant effect on employee performance, and job crafting mediates organizational commitment on employee performance. The higher the level of application of job crafting, the greater the effect of organizational commitment on employee performance.